Measuring the reactivity of a silicon-terminated probe - Sweetman, Adam; Stirling, Julian; Jarvis, Samuel Paul; Rahe, Philipp; Moriarty, Philip (American Physical Society, 2016)
It is generally accepted that the exposed surfaces of silicon crystals are highly reactive due to the dangling bonds which protrude into the vacuum. However, surface reconstruction can not only modify the reactivity of bulk silicon crystals, but plays a key role in determining the properties of silicon nanocrystals. In this study we probe the reactivity of silicon clusters at the end of a scanning probe tip by examining their interaction with closed shell fullerene molecules. Counter to intuitive expectations, many silicon clusters do not react strongly with the fullerene cage, and we find that only specific highly oriented clusters have sufficient reactivity to break open the existing carbon-carbon bonds.